Food Technology - Dinicoli, Barbara; Simpson, Meryl;Fehners, Val;White, Bob (London, United Kingdom : Hodder Education, 2009)
Offering complete coverage of the GCSE design & technology food technology course, this textbook helps students develop knowledge and understanding of the changing food trends, consumer preference and dietary needs and the importance of a balanced diet.
Chapter 1: Design Process -- Chapter 2: Diet and Nutrition -- Chapter 3: Nutrients Found in and Structure of a Common Range of Foods -- Chapter 4: Function of Ingredients -- Chapter 5: Processes and Skills -- Chapter 6: Using Tools and Equipment -- Chapter 7: Preservation and extending shelf life -- Chapter 8: Health and Safety -- Chapter 9: Industrial Production -- Chapter 10: Product Analysis -- Chapter 11: Sustainable Design -- Chapter 12: Controlled Assessment Unit A521 - Introduction to Designing and Making -- Chapter 13: Unit A522 - Sustainable Design -- Chapter 14: Controlled Assessment Unit A523 - Making Quality Products -- Chapter 15: Unit A524 - Technical Aspects of Designing and Making
Includes index.
Keywords: FOOD INDUSTRY AND TRADE